B3LYP Study on Reduction Mechanisms from O2 to H2O at the Catalytic Sites of Fully Reduced and Mixed-Valence Bovine Cytochrome 𝑐 Oxidases - Yasunori Yoshioka; Masaki Mitani (Bioinorganic Chemistry and Applications)
Reduction mechanisms of oxygen molecule to water molecules in the fully reduced (FR) and mixed-valence (MV) bovine cytochrome 𝑐 oxidases (C𝑐O) have been systematically examined based on the B3LYP calculations. The catalytic cycle using four electrons and four protons has been also shown consistently. The MV C𝑐O catalyses reduction to produce one water molecule, while the FR C𝑐O catalyses to produce two water molecules. One water molecule is added into vacant space between His240 and His290 in the catalytic site. This water molecule constructs the network of hydrogen bonds of Tyr244, farnesyl ethyl, and Thr316 that is a terminal residue of the K-pathway. It plays crucial roles for the proton transfer to the dioxygen to produce the water molecules in both MV and FR C𝑐Os. Tyr244 functions as a relay of the proton transfer from the K-pathway to the added water molecule, not as donors of a proton and an electron to the dioxygen. The reduction mechanisms of MV and FR C𝑐Os are strictly distinguished. In the FR C𝑐O, the Cu atom at the CuB site maintains the reduced state Cu(I) during the process of formation of first water molecule and plays an electron storage. At the final stage of formation of first water molecule, the Cu(I) atom releases an electron to Fe-O. During the process of formation of second water molecule, the Cu atom maintains the oxidized state Cu(II). In contrast with experimental proposals, the K-pathway functions for formation of first water molecule, while the D-pathway functions for second water molecule. The intermediates, PM, PR, F, and O, obtained in this work are compared with those proposed experimentally.